Pseudo-coordination and multiple agreement constructions - Giusti, Giuliana; Di Caro, Vincenzo Nicolò; Ross, Daniel (Daniel John), 1988- (Linguistik Aktuell/Linguistics Today Ser., 2022)
"Verbal Pseudo-Coordination (as in English 'go and get') has been described for a number of individual languages, but this is the first edited volume to emphasize this topic from a comparative perspective, and in connection to Multiple Agreement Constructions more generally. The chapters include detailed analyses of Romance, Germanic, Slavic and other languages. These contributions show important cross-linguistic similarities in these constructions, as well as their diversity, providing insights into areas such as the morphology-syntax and syntax-semantics interfaces, dialectal variation and language contact. This volume establishes Pseudo-Coordination as a descriptively important and theoretically challenging cross-linguistic phenomenon among Multiple Agreement Constructions and will be of interest for specialists in individual languages as well as typologists and theoreticians, serving as a foundation to promote continued research"--